Effect of Promotion Strategy on KFC Lampung Purchase Decisions with Purchase Intention as Mediating Variable - Zul, Sulthon Fawwaz; Kusumawati, Richa; Dewi, Rosma (Journal of Islamic Economic Scholar, 2020)
Kentucky fried chicken (KFC) is a franchise company that implements a mix of promotion strategies with components that are considered influential in influencing consumer buying interest. KFC provides a menu in the form of fast food or ready-to-eat food, including fried chicken, french fries, burgers, spaghetti and carbonated drinks and so on. There are various forms of promotion from KFC restaurants, ranging from advertising in various media, both visual, audio and even magazines, billboards and air shows.  This study aims to examine the effect of promotional strategies on consumer purchases with purchases intention as a mediating variabel. The method used in this study used 100 respondents. Statistical tests were performed using PLS-based Structural Equation Modeling. The validation test uses the loading factor value,while the reliability test uses the cronbach’s alpha value. And the result of this study are the Effect of Promotion Strategies on Consumer Purchases at KFC Kedaton Branch has a Significant Effect with Purchase Interest As a Mediation Variabe.Keywords : Promotion strategy, Buying Decisions,Purchases Interes, Buying Interest